The distributional effects of fiscal consolidation in nine EU countries - Silvia Avram; Francesco Figari; Chrysa Leventi; Horacio Levy; Jekaterina Navicke; Manos Matsaganis; Eva Militaru; Alari Paulus; Olga Rastringina; Holly Sutherland (University of Essex, Institute for Social and Economic Research (ISER), 2013)
We compare the distributional effects of policy changes presented as fiscal consolidation measures in nine EU countries that experienced large budget deficits following the financial crisis of the late 2000s and subsequent economic downturn, using the EU microsimulation model EUROMOD. The nine countries, Estonia, Greece, Spain, Italy, Latvia, Lithuania, Portugal, Romania and the UK, chose different policy mixes to achieve varying degrees of fiscal consolidation. We find that the burden of fiscal consolidation brought about through the first round effects of increases in personal taxes, cuts in spending on cash benefits and reductions in public sector pay is shared differently across the income distribution in the nine countries. In Greece, Spain, Italy, Latvia, Romania and the UK the better off lose a higher proportion of their incomes than the poor. At the other extreme, in Estonia, the poor lose a higher proportion than the rich. In Lithuania and Portugal the burden of fiscal consolidation falls more heavily on the poor and the rich than it does on those with middle incomes. Including increases in VAT alters the comparative picture by making the policy packages appear more regressive, to varying extents.
Keywords: C81; H55; I3; 330; austerity measures; European Union; fiscal consolidation; income distribution; microsimulation